2010
DOI: 10.1186/1471-2407-10-560
|View full text |Cite
|
Sign up to set email alerts
|

The multikinase inhibitor Sorafenib displays significant antiproliferative effects and induces apoptosis via caspase 3, 7 and PARP in B- and T-lymphoblastic cells

Abstract: BackgroundTargeted therapy approaches have been successfully introduced into the treatment of several cancers. The multikinase inhibitor Sorafenib has antitumor activity in solid tumors and its effects on acute lymphoblastic leukemia (ALL) cells are still unclear.MethodsALL cell lines (SEM, RS4;11 and Jurkat) were treated with Sorafenib alone or in combination with cytarabine, doxorubicin or RAD001. Cell count, apoptosis and necrosis rates, cell cycle distribution, protein phosphorylation and metabolic activit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
37
0
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(43 citation statements)
references
References 45 publications
(54 reference statements)
3
37
0
3
Order By: Relevance
“…In a study published by Ki et al [27], it was confirmed that apoptosis occurred via the caspase-linked pathway and that drug-induced apoptosis was reduced when a caspase-3 inhibitor was added to HL-60 cells. Our study with leukemic cell lines treated with SOR revealed increased caspase-3 activation, which was consistent with previous results [3,17,19]. LiCl applied to leukemic cell lines has also been demonstrated to prompt an apoptotic response through increased caspase-3 activation [21].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In a study published by Ki et al [27], it was confirmed that apoptosis occurred via the caspase-linked pathway and that drug-induced apoptosis was reduced when a caspase-3 inhibitor was added to HL-60 cells. Our study with leukemic cell lines treated with SOR revealed increased caspase-3 activation, which was consistent with previous results [3,17,19]. LiCl applied to leukemic cell lines has also been demonstrated to prompt an apoptotic response through increased caspase-3 activation [21].…”
Section: Discussionsupporting
confidence: 93%
“…We found a time-dependent decrease in tumor cell proliferation with the administration of the drugs, and binary drug therapy caused the greatest reduction. SOR applied to APL cells has been reported to reduce the number of cells [3,[16][17][18][19]. Consistent with our findings, lithium preventing carcinogenesis in APL cells and various cell lines has also been seen in current studies in the literature [20,21,15].…”
Section: Discussionsupporting
confidence: 92%
“…Both activated caspase-8 and caspase-9 activate common downstream caspases, mainly caspase-3 and caspase-7, and then apoptosis takes place [31]. PARP is reported to be one of the main cleavage targets of caspase-3 in vivo [32]. It was also shown that caspase 7, which shares the same substrate preference as caspase 3, can cleave PARP more efficiently [33].…”
Section: Discussionmentioning
confidence: 92%
“…2E) which further cleaved full length PARP1 (116 kDa) to its inactive 89 kDa fragment (p89/p116; P <0.01 versus CON; Fig. 2E), thereby attenuating the DNA repair function of PARP1 [31]. MEL co-treatment resulted in inhibition of ATR-induced DNA fragmentation, as evident from suppression of the cleavage of caspase-3 (p17/p32; P <0.05 versus ATR) and PARP1 (p89/p116; P <0.05 versus ATR; Fig.…”
Section: Resultsmentioning
confidence: 97%